Gamification in the Workplace: The Central Role of the Aesthetic Experience. Issue 1 (2nd January 2017) - Suh, Ayoung; Cheung, Christy M.K.; Ahuja, Manju; Wagner, Christian
Abstract: Although gamification in the workplace is burgeoning, organizations frequently have difficulty sustaining user engagement with a gamified information system (IS). The focus of this study is how a gamified IS in the workplace engages users and encourages them to continue system use. By proposing the concepts of flow experience (FE) and aesthetic experience (AE) as different ways to provide deep and meaningful user engagement, this study develops a model that explores the antecedents of FE and AE and their roles in explaining an individual's continuance intention to use of a gamified IS. The model is tested using data collected from 178 users of a gamified IS in a global consulting company. The results demonstrate that although FE and AE are complementary forces, AE is more salient than FE for explaining continuance intention. The research proposes AE as a parsimonious yet powerful construct that extends the research on user engagement. The findings contribute to research on gamification by shifting scholarly attention from deep engagement characterized by FE to meaningful engagement characterized by AE.